Design and Self-Assembling Behaviour of Calamitic Reactive Mesogens with Lateral Methyl and Methoxy Substituents and Vinyl Terminal Group - Bubnov, Alexej; Cigl, Martin; Penkov, Deyvid; Otruba, Marek; Pociecha, Damian; Chen, Hsiu-Hui; Hamplová, Věra (Polymers, 2021)
Smart self-organising systems attract considerable attention in the scientific community. In order to control and stabilise the liquid crystalline behaviour, and hence the self-organisation, the polymerisation process can be effectively used. Mesogenic units incorporated into the backbones as functional side chains of weakly cross-linked macromolecules can become orientationally ordered. Several new calamitic reactive mesogens possessing the vinyl terminal group with varying flexible chain lengths and with/without lateral substitution by the methyl (methoxy) groups have been designed and studied. Depending on the molecular structure, namely, the type and position of the lateral substituents, the resulting materials form the nematic, the orthogonal SmA and the tilted SmC phases in a reasonably broad temperature range, and the structure of the mesophases was confirmed by X-ray diffraction experiments. The main objective of this work is to contribute to better understanding of the molecular structure-mesomorphic property relationship for new functional reactive mesogens, aiming at further design of smart self-assembling macromolecular materials for novel sensor systems.
Keywords: reactive mesogen; smectic phases; vinyl group; liquid crystal; self-assembling behaviour